The Relationship of Knowledge Level With The Ability of Football Basic Technical Skills In Extracurricular Students of SMPN 5 Karawang Barat - Muhammad Fikry Rosyadi; Febi Kurniawan; Abdul Salam Hidayat (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2022)
The Relationship between Knowledge Level and Basic Football Technical Skills in Extracurricular Students at SMPN 5 Karawang Barat. This study aims to determine the relationship between the level of knowledge and the basic technical skills of extracurricular soccer students at SMPN 5 Karawang Barat. This research is quantitative research with correlational techniques. The population in this study were students who took part in football extracurricular activities at SMPN 5 Karawang Barat, with as many as 30 students. The sample in this study used a total sampling technique. The technique of collecting data is through a knowledge level questionnaire and a basic football technique skill questionnaire with product-moment correlation techniques and simple linear regression.  The results achieved in the study are that there is a positive relationship between the level of knowledge and basic football technical skills, rxy 0.405, and there is an R-square value of 0.164 or 16.4%, which means that the level of knowledge affects basic technical skills by 16.4%. From the results of this study, it can be concluded that there is a relationship between the level of knowledge and basic technical skills of students in learning football extracurricular physical education at SMPN 5 Karawang Barat. Some suggestions related to this research include: 1) The school should be more supportive of extracurricular football activities at school, especially in facilities or infrastructure suggestions so that they are not too behind in achievements with other schools and can further develop the interest of students to take part in activities football extracurricular. 2) Coaches should be more aware of how students can be more interested in participating in extracurricular football activities. 3) For parents to pay more attention to the potential of children in sports, especially soccer and are expected to encourage children to be more advanced or maybe achieve. 4) Readers, especially teachers, would like to point out that the advantages and disadvantages of extracurricular activities at SMPN 5 Karawang Barat are to be corrected.